Software development for real-time weed colour analysis - Wan Ismail, Wan Ishak; Abdul Rahman, Khairuddin (Universiti Putra Malaysia Press, 2010)
The application of computer and machines for agricultural production has been one of the outstanding developments in Malaysian agriculture, especially in overcoming labour shortages in Oil Palm plantations. The on-line automated weedicide sprayer system was developed at Universiti Putra Malaysia to locate the existence and intensity of weeds in real-time environment and to spray the weedicides automatically and precisely. During the start of the spraying operation, the web camera will initially capture the image of weeds. The computer programme will compute the red, green, blue (RGB) values in the form of computer pixel. These values will be used as reference RGB values to be compared with the RGB values of the weeds captured real-time during the spraying operation. The sprayer nozzle will be turned 'on' or 'off', depending on the percentage or intensity of the green colour pixel value of weeds. The sprayer valve will open the nozzle/s when the camera detected the presence of weeds. The purpose is to reduce wastage, reduce labour, reduce cost, and control environment hazard.